Adolescent health & wellness - 20160731 frey50; Moglia, Paul (Ipswich, MA Salem Press, 2015)
Set description: Covers all aspects of adolescent health and wellness, broken down into three major areas that typically affect adolescents: physical and emotional issues; non-health topics with tremendous potential impact, like safe sex, paying for college, bullying, and leadership; and socially relevant issues, like shopping locally and recycling.
Volume 1. Advice from Teens-Grief and Loss -- volume 2. Health and Illness: Diseases and Conditions-Relationships: Friends, Family, and Dating -- volume 3. School and Jobs: Skills for Success-Your Emotional and Mental Health.
Keywords: Teenagers -- Health and hygiene; Health behavior in adolescence; Teenagers -- Mental health; Teenagers -- Drug use; Teenagers -- Sexual behavior; Teenagers; HEALTH & FITNESS -- Healthy Living; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Preventive Medicine; Encyclopedias